On subclasses of bi-convex functions defined by Tremblay fractional derivative operator - SÜMER EKER, Sevtap; ȘEKER, Bilal (Studia Universitatis Babeș-Bolyai Mathematica, 2019)
We introduce and investigate new subclasses of analytic and bi-univalent functions defined by modified Tremblay operator in the open unit disk. Also we obtain upper bounds for the coefficients of functions belonging to these classes. Mathematics Subject Classification (2010): 30C45, 30C50, 30C80.